An analysis of Nigeria's environmental vision 2010 (2005)
"The Vision 2010 Committee was inaugurated in 1996, with a mandate to develop a blueprint of measures to ensure the realization of Nigeria's potential as an independent country by the year 2010. The Committee submitted its report in 1997. This paper analyses the basic policy objectives-to seek a safe and healthy environment that secures the economic and social well-being of present and future generations—and the strategies used for their achievement. Despite this policy thrust, an in-depth assessment based on facts and figures show that environmental protection/conservation is very low on the nation's agenda. Indeed, the depletion of the forest has continued unabated, such that there is a high rate of deforestation and forest resource loss without a corresponding afforestation programme. The problem of erosion has received little or no attention, given inadequate funding and poor management practices. Very little effort is being made to combat the twin problems of desertification and drought. Pollution from mining and industrial activities is on the increase. Pollution from petroleum (oil spills), particularly from sabotage and blockage, is also on the increase. However, the incidence of gas flaring may be eliminated by the year 2005, given the current trend. Apart front these, Nigeria has developed only about 40 per cent of its water resources. Municipal solid waste is a common feature in most urban centres without corresponding management practices, while environmental planning, and especially Environmental Impact Assessments (EMA), have received little or no attention. Thus, most of the policy objectives are unlikely to be achieved within the stipulated time given the current trends and the general lack of public enlightenment/awareness on the issues of environmental problems and the mitigating measures. A more pragmatic approach is necessary if the policy objective is to be achieved."